2021
DOI: 10.3390/life11111243
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fat Distribution on the Inflammatory Response of Multiple Trauma Patients—A Retrospective Study

Abstract: Objectives In recent years; increasing evidence pointed out the clinical importance of adipose tissue (AT) distribution in various patient populations. In particular, visceral adipose tissue (VAT), when compared to subcutaneous adipose tissue (SAT), was found to play a pivotal role in the development of inflammatory reaction. The aim of the present study was to examine whether body fat distribution has an impact on the development of systemic inflammatory response syndrome (SIRS) in patients with polytrauma. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Two prior studies have shown that visceral to subcutaneous adipose tissue distribution was not associated with increased inflammatory profiles or clinical outcomes after trauma [ 40 , 41 ]. However, a recent study found that lower visceral to subcutaneous adipose tissue distribution was associated with increased inflammatory response and worse clinical outcomes in multiple trauma patients [ 28 ]. In this study, we have examined whether body fat distribution by calculating the VATI/SATI ratio has an impact on abdominal trauma patients as well, but no significant associations were found between the VATI/SATI ratio and clinical outcomes ( Supporting information Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prior studies have shown that visceral to subcutaneous adipose tissue distribution was not associated with increased inflammatory profiles or clinical outcomes after trauma [ 40 , 41 ]. However, a recent study found that lower visceral to subcutaneous adipose tissue distribution was associated with increased inflammatory response and worse clinical outcomes in multiple trauma patients [ 28 ]. In this study, we have examined whether body fat distribution by calculating the VATI/SATI ratio has an impact on abdominal trauma patients as well, but no significant associations were found between the VATI/SATI ratio and clinical outcomes ( Supporting information Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…We further calculated fat-to-muscle area ratios including the total fat-to-muscle area ratio (FTI/SMI), subcutaneous fat-to-muscle area ratio (SATI/SMI), and visceral fat-to-muscle area ratio (VATI/SMI) to assess the combined effects of fat and skeletal muscle on abdominal trauma patients [ 27 ]. In addition, the visceral-to-subcutaneous fat area ratio (VATI/SATI) was computed to evaluate the impact of fat distribution on trauma patients [ 28 ]. All these indices were divided into low and high groups according to sex-specific median cutoff values [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…State‐of‐the‐art image segmentation tools can automatically differentiate subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), and muscle tissue, represented as skeletal muscle index (SMI) and psoas muscle index (PMI) 19 . This body composition analysis (BCA) enables the identification of risk factors based on muscle and fat distribution and has been used successfully in the evaluation of the inflammatory response after polytrauma and also in areas such as oncological surgery and organ transplantation 20–22 . For example, in oesophageal cancer, body composition has been shown to predict severe complications, prolonged hospitalization, and overall survival, 20,23 and in elderly kidney transplant recipients, obesity and sarcopenia are significant risk factors for 1‐ and 5‐year transplant survival, respectively 21 .…”
Section: Introductionmentioning
confidence: 99%
“…11 The injury severity score (ISS) is an established tool for initial trauma assessment and can be used for risk stratification. After calculation of the overall score, trauma patients can be grouped into different ISS categories: mild (ISS 1-3), moderate (ISS 4-8), serious (ISS 9-15), severe (16)(17)(18)(19)(20)(21)(22)(23)(24), and critical . A higher ISS category is associated with poorer outcome in terms of mortality and morbidity and longer hospitalization after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two publications deal with the inflammatory response after multiple traumas. In a retrospective study, Chen et al evaluated the effect of fat distribution (visceral adipose tissue vs. subcutaneous adipose tissue) on the development of systemic inflammatory response syndrome in multiple trauma patients [ 7 ]. The results showed that lower visceral adipose tissue is associated with increased inflammatory response and worse clinical outcome in patients with polytrauma.…”
mentioning
confidence: 99%